Neuromuscular and acute symptoms responses to progressive elastic resistance exercise in patients with chronic obstructive pulmonary disease: Cross-sectional study - Calatayud, Joaquin; Torres-Castro, Rodrigo; Vera-Uribe, Roberto; Olivares-Valenzuela, Álvaro; Guzmán-González, Benjamín; Torres, María E.; Sepúlveda-Cáceres, Nicolás; Andersen, Lars L.; Cruz-Montecinos, Carlos (Frontiers in Medicine, 2022)
Background: Quadriceps muscle training is a key part in rehabilitation of Chronic obstructive pulmonary disease (COPD) patients. However, exercise intensity prescription and progression with the usually used elastic bands is challenging. We aimed to evaluate neuromuscular, acute symptoms and cardiorespiratory responses (heart rate and dyspnea) during progressive elastic resistance exercise in patients with COPD. Methods: Fourteen patients diagnosed with moderate-very severe COPD performed knee extensions at different elastic resistance levels (i.e., colors). The neuromuscular activity was recorded using surface electromyography for the rectus femoris, vastus lateralis and vastus medialis, together with rate of perceived exertion, perceived quadriceps fatigue, dyspnea, oxygen saturation and heart rate. Results: For the vastus lateralis and rectus femoris, increase of muscle activity was evident from a two-level increment when using the red color. For the vastus medialis, there were no muscle activity progressions. Dyspnea, quadriceps fatigue and especially rate of perceived exertion increased in a dose-response fashion and were correlated with the resistance level and muscle activity at the three muscles. Conclusion: Heavy elastic resistance exercise is feasible in COPD patients without excessive dyspnea and stable cardiorespiratory response. In general, at least two elastic resistance increments are needed to enhance muscle activity for the vastus lateralis and rectus femoris, while there is no increase for the vastus medialis. These results may help to individualize exercise dosing during elastic resistance training in patients with COPD.